Introductory statistics for environmentalists - Moore, Paul. (Prentice Hall Europe, 1998)
Written especially for students on degree courses in the environmental sciences and related areas, this much-needed text gives an introduction to and thorough grounding in statistics, and provides an understanding of the importance of the subject in the environmental sciences. This unique text does not assume any prior knowledge, and will provide students with a clear insight into the subject, giving them a firm basis on which to proceed